The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmicb.2021.682754
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Transformation System for Phytophthora cinnamomi Using Green Fluorescent Protein

Abstract: Phytophthora cinnamomi is a destructive pathogen causing root rot and dieback diseases on hundreds of economically and ecologically important plant species. Effective transformation systems enable modifications of candidate genes to understand the pathogenesis of P. cinnamomi. A previous study reported a polyethylene glycol and calcium dichloride (PEG/CaCl2)-mediated protoplast transformation method of P. cinnamomi. However, the virulence of the transformants was compromised. In this study, we selected ATCC 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The growth rate was decreased by approximately 28% compared to the growth recorded for the wild-type LT1534 and CK strains ( Figure 2 ). To generate the complemented (C1) strains, we re-introduced the pTOR-GFP cassette ( Dai et al, 2021 ) containing the full-length PcAPT1 coding (ORF) sequence into the Δ Pcapt1 knock-out mutant, qRT-PCR results have also demonstrated that the expression of PcAPT1 gene in the complemented strain ( Supplementary Figure 1 ). Vegetative growth of the complemented strain is comparable to WT and CK ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The growth rate was decreased by approximately 28% compared to the growth recorded for the wild-type LT1534 and CK strains ( Figure 2 ). To generate the complemented (C1) strains, we re-introduced the pTOR-GFP cassette ( Dai et al, 2021 ) containing the full-length PcAPT1 coding (ORF) sequence into the Δ Pcapt1 knock-out mutant, qRT-PCR results have also demonstrated that the expression of PcAPT1 gene in the complemented strain ( Supplementary Figure 1 ). Vegetative growth of the complemented strain is comparable to WT and CK ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The transformation of Phytophthora spp. has been one method used to deduce the function of effectors; however, some species-such as P. cinnamomi-have had limited success in transformation [66,172,173]. The speculated reasons for these limitations are the identification of oomycete promotors and selectable markers to select for transformants [66,172].…”
Section: Techniques Used In the Functional Characterization Of Phytop...mentioning
confidence: 99%
“…This differs to P. sojae, for which an equal ratio of the two enzymes is used [57]. However, this finding is difficult to compare with most other Phytophthora species, as a wide variety of different enzymes have been used [44,46,64]. My digestion protocol gave protoplast yields of approximately 23 million per culture, comparable to P. sojae [57].…”
Section: Protoplast Production Methodsmentioning
confidence: 91%
“…However, these efforts have not come without challenges. There are numerous reports of difficulty with transformation [46,64] Cas9 toxicity [63,65] and low rates of homozygous editing [63,66]. As of February 2023, CRISPR-Cas genome editing has been reported in five Phytophthora species [57,63,[67][68][69] and three other oomycetes [70][71][72] and will undoubtedly continue to provide insights into Phytophthora biology.…”
Section: Crispr-cas Genome Editingmentioning
confidence: 99%
See 1 more Smart Citation